Effects of spray drying conditions on the physicochemical properties of the Tramadol-Hcl microparticles containing Eudragit® RS and RL - A S Patel; T Soni; V Thakkar; T Gandhi (Wolters Kluwer Medknow Publications, 2012)
The preparation of Tramadol-HCL spray-dried microspheres can be affected by the long drug recrystallization time. Polymer type and drug-polymer ratio as well as manufacturing parameters affect the preparation. The purpose of this work was to evaluate the possibility to obtain tramadol spray-dried microspheres using the Eudragit® RS and RL; the influence of the spray-drying parameters on morphology, dimension, and physical stability of microspheres was studied. The effects of matrix composition on microparticle properties were characterized by Laser Light scattering, differential scanning calorimetry (DSC), X-ray diffraction study, FT-infrared and UV-visible spectroscopy. The spray-dried microparticles were evaluated in terms of shape (SEM), size distribution (Laser light scattering method), production yield, drug content, initial drug loding and encapsulation efficiency. The results of X-ray diffraction and thermal analysis reveals the conversion of crystalline drug to amorphous. FTIR analysis confirmed the absence of any drug polymer interaction. The results indicated that the entrapment efficiency (EE), and product yield were depended on polymeric composition and polymeric ratios of the microspheres prepared. Tramadol microspheres based on Eudragit® blend can be prepared by spray-drying and the nebulization parameters do not influence significantly on particle properties.